Pengaruh Perubahan Tarif Pajak, Tingkat Pendapatan dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM di Kabupaten Gresik - Putri Pinasti; Nyimas Wardatul Afiqoh (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to examine the effect of changes in tax rates, income levels and understanding of taxation on MSME taxpayer compliance. The population in this study are individual taxpayers who have businesses in Gresik Regency. The approach in this research is a quantitative approach. The sampling technique in the research was carried out by the methodpurposive sampling obtained a sample of 58 respondents. The data used is primary data by distributing questionnaires to individual taxpayers who have businesses. Testing data analysis using application assistance SmartPLS Version 3.2.9. The results showed that changes in tax rates had a significant positive effect on MSME taxpayer compliance, income levels had a positive and significant effect on MSME taxpayer compliance and understanding of taxation had a significant positive effect on taxpayer compliance.